Tối ưu tổng quát trong nghiên cứu thực nghiệm máy và ứng dụng vào máy đánh bóng hạt nông sản - Lê, Công Huỳnh (Bộ Giáo dục và Đào tạo, 2013)
Regression experimental design is applied to research on complex objects which are often multifactorial(related to several factors xi and responses Yj). In order to solve optimization problems and determine working regime of machines, as well as find out their optimum design criteria, it's necessary to set up a generalized optimization D-function. All responeses Yj found from experiment data are equalized into functions dj=f(Yj). Then a generalized optimization function is established by addition type (D1 or D2) or by multiphication one(D3). After that, optimum values of Xi-factors will be estimated. This method has been applied to research on DB-1 grain-polishing machine.